1991
DOI: 10.1111/j.1476-5381.1991.tb12493.x
|View full text |Cite
|
Sign up to set email alerts
|

Action of heptaminol hydrochloride on contractile properties in frog isolated twitch muscle fibre

Abstract: 1 Heptaminol stopped or delayed the progressive decline in tension which characterizes the phenomenon of fatigue in frog isolated twitch muscle fibre. 2 Heptaminol had no action on the sodium, potassium and calcium voltage-dependent ionic conductances.3 The hypothesis of an action via an internal alkalinization was tested by comparison with the action of NH4Cl. Both substances increased the tension. 4 The action of heptaminol was suppressed in sodium-free (TRIS) solution or in the presence of amiloride while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…(2) Berthiau et al (1989), in the moderately ischaemic rat isolated heart, have suggested a contribution of an intracellular realkalinization through the Na'-H' exchange process. Recently, the stimulation of the Na'-H' antiport by heptaminol has been evoked to explain its ability to stop the decline in tension in frog isolated twitch muscle fibre (Allard et al, 1991). An alkalinization has also been reported and shown to be concomitant with [Ca2+]i increase in squid giant axon during perfusion with n-alkanols and amines (Vassort et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) Berthiau et al (1989), in the moderately ischaemic rat isolated heart, have suggested a contribution of an intracellular realkalinization through the Na'-H' exchange process. Recently, the stimulation of the Na'-H' antiport by heptaminol has been evoked to explain its ability to stop the decline in tension in frog isolated twitch muscle fibre (Allard et al, 1991). An alkalinization has also been reported and shown to be concomitant with [Ca2+]i increase in squid giant axon during perfusion with n-alkanols and amines (Vassort et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the stimulation of the Na'-H' antiport by heptaminol has been evoked to explain its ability to stop the decline in tension in frog isolated twitch muscle fibre (Allard et al, 1991). An alkalinization has also been reported and shown to be concomitant with [Ca2+]i increase in squid giant axon during perfusion with n-alkanols and amines (Vassort et al, 1986).…”
Section: Effects Of Heptaminol On Ica Recovery From Inactivationmentioning
confidence: 98%
See 1 more Smart Citation
“…Diaphragm muscle stretch was studied with a device and protocol described and provided by Allard B [ 23 ] with several modifications. A bundle from middle part of lateral costal region of the diaphragm was dissected and the tendinous end was left intact while the other end was cut free of the rib and ligated with a fine copper wire for use in mounting preparation.…”
Section: Methodsmentioning
confidence: 99%
“…Diaphragm muscle stretch was studied with a device and protocol described and provided by Allard and Caillé [40,41] with several modi cations. A bundle from middle part of lateral costal region of the diaphragm was dissected and the tendinous end was left intact while the other end was cut free of the rib and ligated with a ne copper wire for use in mounting preparation.…”
Section: In Vitro Diaphragm Contractile Assessmentmentioning
confidence: 99%